Manajemen Sarana dan Prasarana dalam Meningkatkan Mutu Lulusan di MAN 1 Pangandaran - Nova Merisa (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This research focuses on the management of facilities and infrastructure in improving the quality of graduates at MAN 1 Pangandaran.This research uses qualitative methods, with the research subjects being the school principal, deputy head of the madrasa for facilities and infrastructure, homeroom teacher and students. The research was carried out at MAN 1 Pangandaran. The data collection techniques used in this research were observation, interviews and documentation carried out directly in the field. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the research can be concluded, in the facilities and infrastructure management process carried out by the school in improving the quality of graduates at MAN 1 Pangandaran, namely: a) carrying out analysis and planning of the needs for facilities and infrastructure, b) carrying out procurement in accordance with the planned needs for facilities and infrastructure, c)inventory or recording of existing facilities and infrastructure at MAN 1 Pangandaran, d) storage of facilities and infrastructure in accordance with existing procedures, e) carrying out maintenance of facilities and infrastructure, f) eliminating facilities that are no longer suitable for use and carrying out repairs if the facilities are in a condition of minor damage, and g) supervision and evaluation is carried out so that the facilities and infrastructure management process is carried out properly and correctly and reporting to the parties concerned.